The development of a web-based car rental business management system / Wan Fariza Wan Abdul Rahman and Nur Izzan Nadia Mohd Rusli - Wan Abdul Rahman, Wan Fariza; Mohd Rusli, Nur Izzan Nadia (Universiti Teknologi MARA, Kelantan, 2023)
A car rental service is essential, especially in areas with less available public transport. For example, out-campus students need transportation to attend classes in campus areas. Even in a tourism area, car rental service is crucial. Despite relying on public transport, tourists can rent a car and enjoy their trips without being tied to the public transport schedule. However, manual car rental booking is risky for car owners and customers. In case of accidents or a car being stolen, it would be difficult for the car owner to track the customers' data. On the customers' side, it is crucial to protect their rights by getting the best-expected service from money spent. This includes their preferred choice of car, price, and the car's condition. In this article, a one-stop center web-based car rental system is proposed to assist car owners in managing their car rental business while providing customers with an easy booking process.